Pengujian Kekerasan dan Struktur Mikro Sambungan Low-Carbon Steel dan Austenitic Stainless Steel - Nugroho Pratomo Ariyanto; Andy Parulian Siregar; Hanifah Widiastuti; Wowo Rossbandrio; Aulia Fajrin; Cahyo Budi Nugroho (Politeknik Negeri Batam, 2022)
High residual stress can occur in stainless steel and carbon steel weld joints due to difference of thermal expansion coefficients. Corrosion-resistant and mechanical properties of weld joint is affected by stainless steel sensitization, resulted by chromium carbide precipitation, and carbon diffusion on heat-affected zone. This study is conducted to investigate post-weld heat treatment effects of stainless steel 316 and AISI 1018 weld joint with 309L filler metal. As the post-weld heat treatment temperature rises between 400 and 700°C, the hardness value decreases. Observed microstructure of heat-affected zone shows dominance of ferrite phase which experiencing grain growth.